Oxidation of N, N, N, 2, 2, 6, 6‐Heptamethyl‐piperidine‐4‐ammonium Chloride to Water‐Soluble N‐Oxyl Radicals: A Comparative Study. Issue 26 (13th July 2022) - Schröter, Erik; Rohland, Philip; Schreyer, Kristin; Friebe, Christian; Hager, Martin D.; Schubert, Ulrich S.
Abstract: A vast variety of oxidation procedures is known to obtain 2, 2, 6, 6‐tetramethylpiperidinyl‐4‐oxyl (TEMPO) moieties from its piperidinyl precursor. However, up to now no comprehensive study has been performed concerning the performance and feasibility for lab‐scale synthesis. With the focus on the ease of synthesis, occurring impurities, the reaction yield and the degree of oxidation (DoO), this study represents a thorough investigation of different oxidation processes yielding N ‐oxyl radicals in a one‐step procedure. The resulting materials were investigated by redox titration and electron spin resonance spectroscopy to determine the DoO, which is the determining parameter for the yield of this oxidation reaction. The most promising procedures have been transferred to a polymeric material to evaluate the feasibility of the catalysts for more complex substrates. Abstract : In this contribution, catalytic and non‐catalytic reaction procedures are investigated for the oxidation of N, N, N, 2, 2, 6, 6‐heptamethyl‐piperidine‐4‐ammonium chloride. The resultant degree of oxidation was assumed as the defining characteristic, as most literature procedures do not feature purification steps, and inorganic impurities are often ignored. In addition, oxidation procedures were adapted to a polymeric substrate that represents an alternative to standard redox‐flow‐battery materials.